Residencia universitaria green book (2019)
Objectives General objective to propose an architectural proposal focused on the university students and teachers of the communities, 11 laureles and the commune 7 Robledo, in Medellín, creating a student residence that gives an answer to the problematic of this social group, in order to favor general living conditions, contributing to improve and maintain their academic performance. SPECIFIC OBJECTIVES Design the architectural proposal of housing for etudents and educators from universities near the project. Establish alliances with universities for offer of housing